NCMP-04. COMBINATION BRAF/MEK INHIBITION IMPROVES SURVIVAL WITH LEPTOMENINGEAL DISEASE FROM MELANOMA IN A SINGLE INSTITUTIONAL REVIEW AT MOFFITT CANCER CENTER. (14th November 2022) - Wallace, Gerald; Kundalia, Ronak; Imran, Amna; Smalley, Inna; Pina, Yolanda; Forsyth, Peter
Abstract: Melanoma is third most common cancer to metastasize to the leptomeningeal space and confers a dismal prognosis. We retrospectively identified 87 cases of melanoma related leptomeningeal disease (M-LMD) diagnosed between 2011-2020 at Moffitt Cancer Center. The average age at diagnosis was 54 years (range 28-93 years) with a male predominance (50 men vs 36 women). There was a significant increase in median overall survival (OS) for patients with BRAF V600E mutation, but only if they were treated with combined BRAF/MEK inhibitors after diagnosis of LMD (5.54 months vs 1.39 months; p < 0.01). Immune checkpoint inhibitors also associated with a small but significant increase in OS when given after diagnosis of M-LMD (2.73 months vs 1.38mths; p < 0.01). There was no association between OS and gender (p > 0.05). The current data supports use of BRAF/MEK inhibitors for treatment of BRAF V600E mutated M-LMD. More work is needed to improve OS for these patients and patients without a targetable mutation and M-LMD.